2010
DOI: 10.1063/1.3459978
|View full text |Cite
|
Sign up to set email alerts
|

Threshold voltage control in organic thin film transistors with dielectric layer modified by a genetically engineered polypeptide

Abstract: Precise control over the threshold voltage of pentacene-based organic thin film transistors was achieved by inserting a genetically engineered quartz-binding polypeptide at the semiconductor-dielectric interface. A 30 V range was accessed with the same peptide by adjusting the pH of the solution for peptide assembly while leaving other device properties unaffected. Mobility of 0.1–0.2 cm2 V−1 s−1 and on/off current ratio of >106 could be achieved for all devices regardless of the presence of the neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…B) Current–voltage transfer curves obtained for pentacene OFETs modified with QBP assembled under basic (green diamond), neutral (blue circles), and acidic (red triangles) conditions. Reproduced with permission . Copyright 2010, AIP Publishing LLC.…”
Section: Dielectrics Surface Modification Strategies For Organic–biolmentioning
confidence: 99%
“…B) Current–voltage transfer curves obtained for pentacene OFETs modified with QBP assembled under basic (green diamond), neutral (blue circles), and acidic (red triangles) conditions. Reproduced with permission . Copyright 2010, AIP Publishing LLC.…”
Section: Dielectrics Surface Modification Strategies For Organic–biolmentioning
confidence: 99%
“…Other groups have focused on tuning the charge of the insulator/ semiconductor interface or electric field by modifying the interfaces between the dielectric layer and semiconductor layer through the use of oxygen plasma irradiation, 8 UV ozone irradiation, 9 self-assembled monolayers (SAMs), 10,11 or organic materials with molecular polarity. 12 However, these methods could lead to changes in not only V TH but also in mobility, stability, and hysteresis, owing to the influence of charges within the gate dielectric. [13][14][15] Recently, Park et al reported that the flat-band voltage of metal insulator semiconductor (MIS) capacitors was correlated with the work function (W.F.)…”
mentioning
confidence: 99%
“…Direct interfacing of biomolecules with an electronic transducer opens to wider scenarios and an interesting approach encompasses the use of DNA (14) as gate dielectric material or silk for conformal biointegrated electronics (15). Likewise, the modification of a silica surface with quartz binding polypeptides has been proposed to control the OFET turn-onbias (threshold voltage, V T ) (16).…”
mentioning
confidence: 99%